PIBIC-EM na UFSCar: impactos na formação de estudantes da rede pública - Polido, Mariáh (Universidade Federal de São Carlos, 2025)
This study investigated the Institutional Program of Scientific Initiation Scholarships for High School Students (PIBIC-EM) at the Federal University of São Carlos (UFSCar), analyzing its development from its inception through the 2023-2024 cycle, with an emphasis on its role as a public policy for inclusion and scientific training. The research included a documentary analysis of annual public calls and fieldwork through a structured questionnaire aimed at understanding the program's impacts on academic performance, participants' life projects, and personal development. The findings indicate that PIBIC-EM facilitates the integration of public school students into the academic environment, promoting scientific literacy and fostering autonomy. Furthermore, the program contributes to social and educational inclusion by providing opportunities for public school students, thereby enhancing access to scientific and higher education. The study also aims to provide a foundation for future research that explores the subjective dimensions of participants' experiences, offering deeper insights into the socio-emotional and cognitive impacts of the program. While the study acknowledges the program's positive outcomes, it also underscores the need for further investigation into strategies for enhancing the experience and outcomes of the program. In conclusion, PIBIC-EM represents a transformative initiative capable of democratizing access to science and fostering equitable education, highlighting the importance of investing in scientific initiation programs within basic education and expanding this approach within the basic education curriculum.
PIBIC-EM at UFSCar: impacts on the education of public school students
Keywords: Iniciação científica; Projeto de vida; Alfabetização científica; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM